Evaluation of effective operation parameter on High Efficiency Particulate Air and Ultra Low Particulate Air filters (Journal of Civil Engineering Researchers, 2023)
The particle penetration removal efficiency of the High Efficiency Particulate Air (HEPA) and Ultra Low Particulate Air (ULPA) filters were studied by using of mono-disperse liquid aerosols of Di-Octyl Phethalate (DOP) under vary operational conditions. The effects of different operational factors, including the particle size, the face velocity and pressure drop were investigated in this study. The results indicated that the most penetrating particle size through the ULPA and HEPA filters was approximately 0.1-0.12 µm. Brown diffusion effect is suggested mechanism for particle size removal mechanism of 0.1 µm and less while impaction and interception mechanisms are explained the behavior of HEPA and ULPA filters for removal of 0.12 µm and more particle size. The penetrations of particle through both kind of filters were increased with increasing of face velocity. Additionally, the pressure drop of filter is increased versus the rising of face velocity. The cost of energy is lower in low face velocity of filters.
Keywords: HEPA; ULPA; Filtration; Efficiency